IMPLEMENTASI METODE PEMBELAJARAN MIND MAPPING PADA MATA PELAJARAN AKIDAH AKHLAK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IX DI MTs MA'ARIF NU KOTA MALANG - Indah Ayu Nuraini; Chalimatus Sa’dijah; Moh Eko Nasrullah (VICRATINA, 2020)
The problem behind this research is the low student learning outcomes in the moral subjects of the ninth grade at MTs Ma'arif NU Malang, so the research applies mind mapping learning methods . The purpose of this study is to determine the application of mind mapping learning methods by teachers during the learning process and to find out the improvement in student learning outcomes during the learning process when using mind mapping learning methods .This study uses a qualitative approach to the type of classroom action research (CAR), conducted in 2 cycles, 4 meetings with the stages of planning, action implementation, observation and reflection. Which is the researcher as a teacher and subject teacher akidak akhalak as a teacher observer during learning takes place. Data collection in this study uses the method of observation, interviews, tests, and documentation during the activity. To determine the ability of teachers to apply mind mapping learning methodsnamely the observation sheet of teacher activities during learning and to find out the improvement of student learning outcomes by giving test questions to students after each learning. From the results of the study show that: 1) there is an increase in the ability of teachers to apply mind mapping learning methods in each cycle, 2) student learning outcomes increase, so that of 21 students achieve KKM scores or a minimum value of 75 overall with a percentage of 100%.